"Questioning the Relationship. Between Children's Spirituality and Traditions". Report on the 16th International Conference on Children's Spirituality - Stockinger, Helena (International journal of children's spirituality, 2019)
The 16th International Conference on Children`s Spirituality "Questioning the Relationship. Between Children`s Spirituality and Traditions" took place from the 24th to th 27th of July 2018 at the Laval University in Quebec, Canada. The report gives a review of the conference and summarizes some findings.